PENGARUH BELANJA DAERAH, PENDAPATAN ASLI DAERAH DAN PERTUMBUHAN EKONOMI TERHADAP KEMISKINAN PADA PEMERINTAH KABUPATEN DAN KOTA DI SUMATERA UTARA - Oktarini Khamilah Siregar (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
This research is to find out the Effect of Regional Expenditures, Regional Original Revenue and Economic Growth on the Ministry of Religion in District and City Governments in North Sumatra. The type of data used is secondary data. The population in this study were 33 regency and city governments in North Sumatra Province, so that the sample analysis unit was 30 research samples (6 districts / cities X 5 years) namely Langkat Regency, Deli Serdang Regency, Serdang Bedagai Regency, Karo Regency, Medan City and The city of Binjai and research were taken from 2013 to 2017. This research was conducted at the Central Sumatra Provincial Statistics Agency (BPS) on No. 1 Dormitory street. 179 Medan. The results of this study according to the hypothesis test show that partially (t test) Regional Expenditures have a significant effect on Poverty In District and City Governments in North Sumatra and Regional Original Income and Economic Growth have no significant effect on Poverty in District and City Governments in North Sumatra. But simultaneously (f test) shows that Regional Expenditures, Regional Original Income and Economic Growth have a significant effect on Poverty in District and District ta in North Sumatra.